2017
DOI: 10.1016/j.rmed.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

FAM13A polymorphism as a prognostic factor in patients with idiopathic pulmonary fibrosis

Abstract: FAM13A gene polymorphism showed a significant association with the susceptibility to IPF, with severity of lung function impairment and with poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
0
18
1
2
Order By: Relevance
“…MUC5B is only one genetic variant associated with the development of IIP. While our findings suggest that the MUC5B variant does not contribute to risk in myositis-ILD, it does not exclude other shared genetic risk factors [17]. Myositis-ILD is likely due to the interaction of multiple genetic risk factors and environmental exposures.…”
Section: Discussioncontrasting
confidence: 79%
“…MUC5B is only one genetic variant associated with the development of IIP. While our findings suggest that the MUC5B variant does not contribute to risk in myositis-ILD, it does not exclude other shared genetic risk factors [17]. Myositis-ILD is likely due to the interaction of multiple genetic risk factors and environmental exposures.…”
Section: Discussioncontrasting
confidence: 79%
“…In the meanwhile, Eisenhut et al () denoted FAM13A was associated with non‐small cell lung cancer (NSCLC) progression and controls tumor cell proliferation and survival. Hirano et al () reported the polymorphism of FAM13A gene had a significant association with the susceptibility to idiopathic pulmonary fibrosis, with severity of lung function impairment and with poor prognosis. However, studies about the FAM13A and other diseases have not been reported, including liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genome-wide association studies identified family with sequence similarity 13, member A (FAM13A) gene as a genetic locus associated with pulmonary function [4], and it is known to be associated with lung diseases including chronic obstructive pulmonary disease (COPD) [5], asthma [6] and pulmonary fibrosis [7][8][9]. Moreover, causative role of FAM13A in the development of COPD has been revealed.…”
Section: Introductionmentioning
confidence: 99%